2011
DOI: 10.1007/s12272-011-1216-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 4′,7-dimethoxyflavanone on cell cycle arrest and apoptosis in human breast cancer MCF-7 cells

Abstract: The present study was designed to investigate the anticancer activity of 4,7-dimethoxyflavanone in vitro. When human breast cancer MCF-7 cells were treated with 4',7-dimethoxyflavanone at various concentrations (1-200 μM) for 24 h, antiproliferative effects were first observed at 1 μM and the IC(50) was 115.62 μM. Conversely, 4',7-dimethoxyflavanone was not cytotoxic (measured as lactate dehydrogenase release in CHO-K1 cells) under the same conditions. MCF-7 cells exposed to the 4',7-dimethoxyflavanone at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…2′-Hydroxy-3,4,4′-trimethoxychalcone ( 2 ) is a compound with a chalcone skeleton, and it has been reported to have many active effects, such as anti-cancer and anti-inflammatory effects [ 40 , 41 ]. 4′,7-Dimethoxyflavanone ( 3 ) is a compound with a flavanone skeleton, reported to have anticancer effects [ 42 ], however there are no reports on its anti-inflammatory activity. 8-Methoxybutine ( 4 ) and leptosidin ( 5 ) are known to have whitening and antioxidant effects and have been reported to be isolated from C. lanceolata [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…2′-Hydroxy-3,4,4′-trimethoxychalcone ( 2 ) is a compound with a chalcone skeleton, and it has been reported to have many active effects, such as anti-cancer and anti-inflammatory effects [ 40 , 41 ]. 4′,7-Dimethoxyflavanone ( 3 ) is a compound with a flavanone skeleton, reported to have anticancer effects [ 42 ], however there are no reports on its anti-inflammatory activity. 8-Methoxybutine ( 4 ) and leptosidin ( 5 ) are known to have whitening and antioxidant effects and have been reported to be isolated from C. lanceolata [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…55 The results of another study, published soon aerwards, explored the antiproliferative effects of synthetic avanone derivatives on human breast cancer cells by way of p53-mediated apoptosis and the induction of cell cycle arrest at the G1 phase. 56 Usman et al had previously reported the cytotoxic activities of avanones isolated from the bark of Cryptocarya costata. 57 A study of eight avanones on colorectal carcinoma cells indicated that 2 0 -OH avanone showed the most potent cytotoxic effect on these cancer cells, and cell death induced by 2 0 -OH avanone, was via the occurrence of DNA ladders, apoptotic bodies, and hypodiploid cells, all characteristics of apoptosis.…”
Section: Benzopyrans and Fused Pyranbased Anticancer Scaffoldsmentioning
confidence: 99%
“…10) are also important ingredients of human diet. 56,[59][60][61][62] Kumar et al established the design and synthesis of naph-thoavones (56-59, Fig. 11).…”
Section: Benzopyrans and Fused Pyranbased Anticancer Scaffoldsmentioning
confidence: 99%
“…Naringin shows the ability of an antioxidant [5,6], as well as its anti-inflammatory [5,7], anti-cancer (breast cancer) [8], anti-allergic [9], and anti-diabetic activities [10,11].…”
Section: Introductionmentioning
confidence: 99%